Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $(V,Q)$ be a finite-dimensional quadratic space over a field $\mathbb{K}$. From my definition, $Q$ is non-degenerate if $\operatorname{rad}(V)=\{0\}$.

How can I prove that $Q$ is non-degenerate iff the matrix associated to the scalar product defined by $Q$ (in any basis of $V$) is non-singular?

Surely this is trivial, but I can't conclude...

share|cite|improve this question
up vote 0 down vote accepted

$$(u,v) = \frac{1}{2}(Q(u+v, u+v) - Q(u) - Q(v)) = u^T B v$$

Letting $u$ vary over all the standard basis vectors, we see that $I^T B v = I B v = Bv = 0$ has a non-trivial solution if and only if $B$ is non-singular.

ie) if $B$ is singular, let $B v = 0$. Then $u^T B v = 0$ for all $u \in V$.

On the other hand $B$ is non-singular, there is no $v$ satisfying $I^T B v = 0$ and so for any $v$, there is some choice of $i$ such that $(e_i, v) \neq 0$.

share|cite|improve this answer

One can make above answer characteristic free by taking $B(u,v)=Q(u+v)-Q(u)-Q(v)$. Note that $\mathrm rad(V)=0$ is condition 2) below.

If $B$ is a bilinear form over a vector space $V$, then note that following are equivalent: 1) The matrix $\{B(e_i,e_j)\}$ is non-singular. 2) $u\mapsto B(~,u)$ defines an isomorphism $V\rightarrow V^*$ 3) For $u\in V$, $B(u,v)=0$ for all $v\in V$ implies that $u=0$.

Proof: 2) implies 3) is straightforward. For 1) implies 2): In this case $\{B(~,e_j)\}$ will form a basis: $\sum a_jB(~,e_j)=0$ implies $\sum a_jB(e_i,e_j)$ for every $i$. Thus $(a_1,\cdots,a_n)$ is in the kernel of matrix $\{B(e_i,e_j)\}$ hence it is zero. Thus we will get 2. Now to show 3) implies 1): we will show that rows of $\{B(e_i,e_j)\}$ are linearly independent. Consider $\sum\alpha_i(B(e_i,e_1),\cdots,B(e_i,e_n))=0$. This will imply $B(\sum_i\alpha_ie_i,e_j)=0$ for every $j$. Hence by 3) $\sum_i\alpha_ie_i=0$, this $\alpha_i=0$ for each $i$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.